ANALISA PENGARUH PANJANG PIPA GALVANIS DAN DIAMETER BUKAAN KATUP TERHADAP HEAD POMPA PADA POMPA HIDRAM - Utomo, Gatut Prijo; Abidin, Khoirul (MEKANIKA: Jurnal Teknik Mesin, 2015)
Hamlet Ketos and hamlets Cabe is 2 (two) of 7 (seven) hamlet in Wonodadi Kulon, Ngadirojo Pacitan, the problems faced by the community, especially for Hamlet Ketos and hamlets pepper the area of hills and rocks areprone / difficulty getting water net. The approach offered to solve the problem is by making a catchment basin,hydraulic ram and tank water divider.Hydraulic ram works on the principle of water hammer. When the fluid flow is stopped suddenly it changes themomentum of the fluid future will increase the pressure suddenly. Increased pressure is used to lift some of thewater to higher ground. Then designed hydraulic ram which uses the potential energy of the water as a vehicle. Indesigning the authors use the pump inlet pipe length variation of 18 meters, 24 meters and 30 meters and a diameterof the valve opening is full (0.1 meters), 0.08 meters and 0.065 meters. Tests carried out in the river, precisely inHamlet and Hamlet Ketos Cabe, Pacitan.It can be concluded at this test that by using a long inlet pipe diameter of 30 meters and full valve opening is 0.1meters and the discharge pump head has more leverage than other tests, namely the pump head 173 m and waterdischarge (output) generated amounted to 6.68 L / min. So the longer the pipe entrance (L), the higher the pressuredihasilakan, as well as thelarger the diameter of the valve opening, the greater the pressure acting on the hydraulicram, because the greater the time and speed, the momentum was also greater, so the impulse weight the exhaustvalve is closed suddenly make a greater boost the flow exceeds the static pressure inlet pipe, and it affects the pumphead on the hydraulic ramKeywords: hydraulic ram, a long inlet pipe, the diameter of the valve opening